Modelos de vulnerabilidade social a desastres - David Alexander (Revista Crítica de Ciências Sociais, 2011)
This paper discusses the bases of theory in the evaluation of social vulnerability to disasters. Vulnerability is shown to be the vital component of risk and the principal element of disaster impacts. Perception is a key process in decision making in disasters. It is affected by culture and symbolism, which are analyzed in the context of disaster risk. A model of cultural metamorphosis is used to explain changes and discrepancies in attitudes to disaster and recovery processes. The response to the L’Aquila (central Italy) earthquake of 6 April 2009 is discussed as an illustration of processes of cultural metamorphosis and symbolic interpretation of disasters. The response was influenced by both modern and inherited cultural traits, which can be identified and analyzed in order to explain public reactions to the event. A new model is proposed in which culture and history combine with physical hazards to influence vulnerability.